Comparative characteristics of biochemical composition of synovial fluid of knee and elbow human joints - E. S. Spirkina (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The purpose of this study was comparative analysis of normal biochemical composition of synovial fluid of knee and elbow human joints. Studies were performed on synovial fluid samples of 33 cadavers of suddenly dead people of both sexes (26 men and. 7 women) at the age of 23 to 79 years, without articular pathology registered by expert. We didn't reveal reliable differences of albumen-globulin coefficient, but there were differences in contents of albumen fractions, products of oxide peroxidation of albumens. At the developement of pathological process cast of albumen in synovial fluid is possibly the compensatory reaction in providing of synovia viscosity, because albumen component provides this function on level with hyaluronic acid. Knee joint is an hinge joint, that is meant to bend only in one plane. Biomechanics of elbow joint is much more complicated and. is described as "ginglymoid hinge" with abduction-adduction besides the joint is much smaller. Obtained results can be used as normative values of biochemical synovial fluid indexes in orthopaedic and. trauma practice